2022
DOI: 10.1186/s12870-022-03820-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of stress-induced calcium signals in the crop species barley and the model plant Arabidopsis thaliana

Abstract: Background Plants are continuously exposed to changing environmental conditions and biotic attacks that affect plant growth. In crops, the inability to respond appropriately to stress has strong detrimental effects on agricultural production and yield. Ca 2+ signalling plays a fundamental role in the response of plants to most abiotic and biotic stresses. However, research on stimulus-specific Ca 2+ signals has mostly been pursued in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…The propagation of a fast salt-induced Ca 2+ wave in the shoot and an osmolyteinduced Ca 2+ wave with a lower amplitude was demonstrated in other studies [51,52]. The root-to-shoot Ca 2+ signal can be induced in various ways: hyperosmolarity can activate mechanosensitive NSCCs and osmosensor reduced-hyperosmolality-induced-[Ca 2+ ] i -increase 1 (OSCA1) [53,54], as well as NSCCs through the generation of ROS by respiratory burst oxidase homologue (RBOH), which is activated by receptor kinase Feronia via Rho-of-plants (ROP) [55,56].…”
Section: Salt-induced Root-to-shoot Signalssupporting
confidence: 63%
“…The propagation of a fast salt-induced Ca 2+ wave in the shoot and an osmolyteinduced Ca 2+ wave with a lower amplitude was demonstrated in other studies [51,52]. The root-to-shoot Ca 2+ signal can be induced in various ways: hyperosmolarity can activate mechanosensitive NSCCs and osmosensor reduced-hyperosmolality-induced-[Ca 2+ ] i -increase 1 (OSCA1) [53,54], as well as NSCCs through the generation of ROS by respiratory burst oxidase homologue (RBOH), which is activated by receptor kinase Feronia via Rho-of-plants (ROP) [55,56].…”
Section: Salt-induced Root-to-shoot Signalssupporting
confidence: 63%
“…In this study, an analysis of the barley transcriptome in response to H 2 O 2 was performed using next generation sequencing. First, a suitable concentration of H 2 O 2 that was shown to initiate a stress response in barley was selected on basis of previously performed experiments ( Dodd et al., 2010 ; Giridhar et al., 2022 ). An increase in cytosolic Ca 2+ ([Ca 2+ ] cyt ) is one of the first responses of plants to most biotic and abiotic stresses ( Dodd et al., 2010 ) that in turn leads to downstream stimulus-specific cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in cytosolic Ca 2+ ([Ca 2+ ] cyt ) is one of the first responses of plants to most biotic and abiotic stresses ( Dodd et al., 2010 ) that in turn leads to downstream stimulus-specific cellular responses. H 2 O 2 was shown to induce such transient changes of [Ca 2+ ] cyt with 10 mM eliciting the highest response in barley roots and leaves ( Giridhar et al., 2022 ). Staining of intact plants with the ROS indicator H 2 -DCFDA confirmed that the exogenously applied H 2 O 2 penetrated into both organs ( Figures 1B, C , Supplementary Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, while transgenic reporter lines are a standard research tool in other model plants, only few fluorescent reporter lines have been generated to gain insight into barley growth and physiology, as e.g. for auxin and cytokinin signalling (Kirschner et al 2018;Amanda et al 2022) or calcium signatures (Giridhar et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While transgenic sensor lines in the model dicotyledon A. thaliana are in use since more than a decade, the progress in other genetically accessible model plants has only recently started to gain momentum (Kirschner et al 2018; Müller-Schüssele et al 2020; Hipsch et al 2021; Giridhar et al 2022). To start filling this gap in temperate cereal crops, we created transgenic barley lines expressing the genetically-encoded redox biosensor cytosolic Grx1-roGFP2 for E GSH .…”
Section: Introductionmentioning
confidence: 99%